APPLICATION OF GOOD CORPORATE GOVERNANCE PRINCIPLES IN IMPROVING BENEFITS OF STATE-OWNED ENTERPRISES (An Emperical Evidence from Indonesian Stock Exchange at Moment of Covid-19) - Nur Ilham, Rico; Arliansyah, Arliansyah; Juanda, Reza; Sinta, Irada; Multazam, Muhammad; Syahputri, Lidia (CV. Radja Publika, 2022)
Restructuring and privatization are important efforts to increase the efficiency and productivity of SOEs. This research aims to formulate strategies in regulating and controlling companies to increase business success while taking into account the interests of stakeholders and reducing agency conflicts in order to achieve company goals. So that investors in the capital market are very concerned about the company's ability to generate, support, and increase profits. Profitability can be measured in several different ways, but in interrelated dimensions. First, there is a relationship between profit and sales so that there is a residual return for the company per rupiah of sales. Return on sales can be in the form of a net profit margin ratio. Liquidity is an indicator of the company's ability to pay all short-term financial obligations at maturity using available current assets. Liquidity is not only related to the overall financial condition of the company, but also relates to the ability to convert certain current assets into cash. This type of research is descriptive quantitative research, namely critical observation to obtain precise information on a particular problem and object in the area of a community group or certain location will be studied or described or described a situation as clearly as possible without any treatment of the object being studied. researched. In this study, the object of research is a state-owned company listed on the LQ45 index on the Indonesia Stock Exchange. and the location of this research is the Indonesia Stock Exchange by accessing its official website through the website www.idx.co.id. The outputs of this research are publications of reputable national journals, and reference books for ISBN certified research results with TKT level 3.